Raising global IQ : preparing our students for a shrinking planet - Hobert, Carl F., 1961- (Boston : Beacon Press, 2013)
"In Raising Global IQ, Carl Hobert calls on K-12 teachers, administrators, parents, and students alike to transform the educational system by giving students the tools they need to become responsible citizens in a shrinking, increasingly interdependent world. Drawing on his nearly thirty years teaching, developing curricula, and leading conflict-resolution workshops here and around the world, he offers creative, well-tested, and understandable pedagogical ideas to help improve our children's GIQ: Global Intelligence Quotient. Cognizant of many U.S. schools' limited budgets and time, Hobert advocates teaching foreign languages early in life, honing students' conflict-resolution skills, providing creative-service learning opportunities, and offering cultural-exchange possibilities in students' own communities, as well as nationally and abroad--all before they graduate from high school"--
Machine generated contents note: pt. ONE Fluencies -- One.The Argument for Starting with Romance Languages -- Two.Targeting an East-West Balance -- Three.Establish Learning Goals First; Harness Technology Second -- Four.Travel Opportunities and the Fluency of Extracurricular Activities -- pt. TWO Action Steps -- Five.Preventive Diplomacy -- Six.The Case Study in Action: Role-Play for Peace -- Seven.Taking the Case Study Global -- Eight.Service Learning: The Power of Experiential Education -- Nine.PEARS: Five Key Aspects of Service Learning -- pt. THREE Building The Global IQ Infrastructure at Your School -- Ten.Global IQ and the Architecture of Educational Transformation.
Includes bibliographical references (p. 181-186) and index.
Keywords: International education; Education and globalization; Moral education; EDUCATION / Philosophy & Social Aspects; POLITICAL SCIENCE / Globalization; EDUCATION / Physical Education; Education and globalization; International education; Moral education